2023
DOI: 10.17219/dmp/157345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between the geriatric anxiety and COVID-19 anxiety and fear levels in geriatric dental patients during the COVID-19 pandemic

Abstract: Background. Illness, social isolation and loneliness may cause different psychological problems in the geriatric population, including depression and anxiety. Factors such as anxiety and fear can negatively affect dental treatment processes and prognoses. Thus, in terms of dental approach to geriatric individuals, it is important to be aware of the emotional processes the elderly may have experienced during the pandemic.Objectives. This study aimed to determine the relationship between the geriatric anxiety le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…21 This finding is explained by a lower awareness of the real threat of the pandemic amongst young people, and reconciliation with fate and the passage of time in the elderly. 22 A different relationship was observed by researchers from Italy, 22 China, 23 Japan, 24 Turkey, 25 and Poland, 7 who showed that the anxiety levels increased with age. The reason for this can be found in the more severe course of viremia, a worse prognosis and numerous complications correlated with the burden of comorbidities in the elderly.…”
Section: Discussionmentioning
confidence: 90%
“…21 This finding is explained by a lower awareness of the real threat of the pandemic amongst young people, and reconciliation with fate and the passage of time in the elderly. 22 A different relationship was observed by researchers from Italy, 22 China, 23 Japan, 24 Turkey, 25 and Poland, 7 who showed that the anxiety levels increased with age. The reason for this can be found in the more severe course of viremia, a worse prognosis and numerous complications correlated with the burden of comorbidities in the elderly.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have reported an increase in anxiety among older adults and a high incidence of COVID-19 anxiety in the elderly following the outbreak. [7][8][9] Advanced age is associated with various diseases and disorders, including mental health conditions, with anxiety being one of the most prevalent. 10 Anxiety significantly affects the lives of the elderly, reducing their quality of life, 11 increasing the risk of developing dementia 12 and cardiovascular diseases, 13 and impairing cognitive function, overall functioning, and sleep patterns.…”
Section: Introductionmentioning
confidence: 99%
“…COVID‐19 anxiety and geriatric anxiety have emerged as negative consequences following the pandemic. Previous studies have reported an increase in anxiety among older adults and a high incidence of COVID‐19 anxiety in the elderly following the outbreak 7–9 . Advanced age is associated with various diseases and disorders, including mental health conditions, with anxiety being one of the most prevalent 10 .…”
Section: Introductionmentioning
confidence: 99%
“…6 According to past studies, widespread COVID-19 was associated with an increase in depression, anxiety, psychological distress and other mental illness, 3,[7][8][9] and led to a projected and international increase in suicide. 10 Those negative mental impacts may also be associated with various risk factors, which include not only the features of social environment such as news accuracy, 11 and governments' reactions and measures, 12 but also people's demography features like age and gender, 3,[13][14][15] educational levels, 15,16 original physical status, 17 cultural backgrounds, 9,15 employment status, 18 and marital status. 9,15,18 These phenomena should receive more attention from psychiatrists across the world, and their causes, correlates, and managing strategies should be researched on.…”
Section: Introductionmentioning
confidence: 99%